PRELIMINARY PHYTOCHEMICAL ANALYSIS OF LEAF EXTRACTS OFTHUJA ORIENTALIS (L.) ENDL - Nguyen Le BaoDuy, Dao Thi Diem Trang, Nguyen Pham Minh Trang. (International Journal of Research Science and Management, 2015)
The objective of the present study was to investigate the presence of various phytochemicals from the methanolic, ethanolic, aqueous and ethyl acetate extracts of leaf extracts ofThujaorientalis (L.) Endl.Preliminary phytochemical screening of the extracts revealed the presence of alkaloids, flavonoids, terpenoids,tannins, phenols, anthraquinone, glycosides,oils and fats, and carbohydrates. The present study provides evidence that solvent extracts of Thujaorientalis (L.) Endlcontains medicinally important bioactive compounds and this justifies the use of plant species as traditional medicine for treatment of various diseases.